Behavioral Aspects and Their Effect on The Implementation Of The Regional Financial Accounting System Of Bojonegoro Regency - Tsania FITRIANA; Anis WULANDARI; Nurul KOMPYURINI (Journal of Governance, Taxation and Auditing, 2022)
ABSTRACT This research aimed to know how the organization’s behavioral aspects affect the region’s application financial accounting system (case studies on BPKAD Bojonegoro Region East Java). Organization’s behavioral aspects are draw from the psychological and social psychological aspects of attitudes, motivations, emotions, perception, and personality. This type of research is a qualitative analysed with a statistical aid Smart PLS 3.0. Collection methods are being obtained through direct colonisation at the BPKAD office in Bojonegoro. Sample retrieval techniques using purposive sampling with nonprobability sampling methods that match the criteria. The total number of employees fit the criteria of 40. This reseach suggests that emotions, perception, and personality influence region’s application financial accounting system. Whereas attitude and motivation do not affect the region’s application financial accounting system. Keywords: Aspects of organizational behavior, regional application financial accounting system, psyhchology, social psychology